Relationship Of Role Conflict And Stress With Performance Of Employees At Seluma Timur District Police Office Seluma Regency - Ngatimin Ngatimin; Ahmad Soleh; Abdul Rahman (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of motivation and job satisfaction simultaneously on employee productivity at PT. Four Lawang Agro Perkasa in Empat Lawang Regency. The sample in this study were employees at PT. Four Lawang Agro Perkasa as many as 35 people. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of the regression analysis show Y = 1.501 + 0.380X1 + 0.603 X2 + 5.900 this describes a positive regression direction, meaning that there is a positive influence between X1 (motivation) and X2 (job satisfaction) on work productivity (Y). Means that if the variables of motivation and job satisfaction increase, it will increase work productivity. The value of the coefficient of determination is 0.590. This means that X1 (motivation) and X2 (job satisfaction) affect work productivity (Y) by 59% while the remaining 41% is influenced by other variables not examined in this study. The test results for the X1 variable (motivation) show the tcount value is greater than ttable at 2,424 > 1,693 and a significance value of 0.021 < 0.05. Because tcount > ttable and the significance value is less than 0.05, then H0 is rejected and Ha is accepted. This means that X1 (motivation) has a significant influence on work productivity (Y) of employees at PT. Four Lawang Agro Perkasa in Empat Lawang Regency. The test results for the X2 variable (job satisfaction) show the tcount value is greater than ttable at 3.258 > 1.693 and a significance value of 0.003 <0.05. Because tcount > ttable and the significance value is less than 0.05, H0 is rejected and Ha is accepted. This means that X2 (job satisfaction) has a significant effect on work productivity (Y) of employees at PT. Four Lawang Agro Perkasa in Empat Lawang Regency. The value of Fcount > Ftable (22,986 > 3,29) with a significant value of 0.000 < 0.05 indicates that simultaneously X1 (motivation) and X2 (job satisfaction) have a significant effect on work productivity (Y) of employees at PT. Four Lawang Agro Perkasa in Empat Lawang Regency.